STUDY TO EVALUATE THE REMOVAL EFFICIENCY OF 2,4-D AND 2,4,5-T IN CONTAMINATED SOIL BY ZERO-VALENT IRON NANOPARTICLES - Duc Pham Viet, Ha Nguyen Thi, Nam Nguyen Hoang (Chelonian Research Foundation, 2024)
In this study 2,4-Dichlorophenoxy-acetic acid (2,4-D) and 2,4,5-Trichlorophenoxyacetic acid (2,4,5-T) in contaminated soil were removed using zero-valence iron nanoparticle material (nZVI), which was prepared by liquid phase reduction method. The nZVI contains 50% 10-20 nm particles and about 86.38% Fe. Soil samples were taken at four sites, with 2,4-D and 2,4,5-T contents of 4.83 - 87.98 ppm and 6.25 - 148.38 ppm, respectively. The sample with the highest concentration and the sample mixed from 4 samples taken at different points were used. With the ratio of nZVI:(2,4-D and 2,4,5-T) is 1:1 (w/w), the amount of polyacrylamid (PAA) of 0.01% and pH 3.0, the removal efficiency increased with time and depended on the initial contents. After 84 day-reaction, the content of 2,4-D and 2,4,5-T decreased from 87.98 to 10.68 and from 148.38 to 29.37 ppm, respectively for highest content samples. For mixed samples, these values were respectively from 39.31 to 3.53 and from 67.85 to 8.48 ppm. The removal efficiency of 2,4-D and 2,4,5-T obtained over 90 and 87.5%, respectively. During the reaction process, 2,4-D and 2,4,5-T were absorbed onto the surface of nZVI, where they were decomposed into 2,4-DCP and 2,4,5-TCP, then further dechlorinated to less toxic compounds e.g. parachlorophenon, phenon and benzene. The nZVI is considered as promising material to remove chlorine-containing organic compounds in soil environment.